2015
DOI: 10.1016/j.vaccine.2014.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Controlling measles using supplemental immunization activities: A mathematical model to inform optimal policy

Abstract: BackgroundThe Measles & Rubella Initiative, a broad consortium of global health agencies, has provided support to measles-burdened countries, focusing on sustaining high coverage of routine immunization of children and supplementing it with a second dose opportunity for measles vaccine through supplemental immunization activities (SIAs). We estimate optimal scheduling of SIAs in countries with the highest measles burden.MethodsWe develop an age-stratified dynamic compartmental model of measles transmission. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 28 publications
(33 reference statements)
0
70
0
Order By: Relevance
“…For example, studies suggest the need for different estimates of optimal ages for RI with MCV due to different types of immunity among women of child‐bearing age (WCBA), with one U.K. analysis of the optimal ages for MCV, RCV, and MRCV assuming a two‐dose RI schedule considering maternal immunity and different assumptions about forces of infection by age for both measles and rubella . Only six studies explicitly considered vaccine failure (i.e., an S1 state), with the earliest of these emphasizing that vaccine failures represent a significant part of the susceptible population in a highly immunized population, and only two studies included an M1 state …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies suggest the need for different estimates of optimal ages for RI with MCV due to different types of immunity among women of child‐bearing age (WCBA), with one U.K. analysis of the optimal ages for MCV, RCV, and MRCV assuming a two‐dose RI schedule considering maternal immunity and different assumptions about forces of infection by age for both measles and rubella . Only six studies explicitly considered vaccine failure (i.e., an S1 state), with the earliest of these emphasizing that vaccine failures represent a significant part of the susceptible population in a highly immunized population, and only two studies included an M1 state …”
Section: Resultsmentioning
confidence: 99%
“…One included study and one excluded study reported that SIAs represent a cost‐effective investment for Uganda. Hypothetical modeling for developing countries showed that regular SIAs offer a strategy to prevent measles outbreaks and characterized the required frequency for SIAs as a function of RI coverage …”
Section: Resultsmentioning
confidence: 99%
“…In particular, the study wanted to identify the rates of vaccination that affected the chances of an outbreak occurring and what the effect of people being unvaccinated was. e dynamic of measles infection transmission in the form of age-stratified compartmental model was developed by Verguet et al [42] aiming at exploration of the frequency of SIAs in order to achieve measles control in selected countries. Beyond the susceptible, infected, and recovered compartments, the model contains three vaccinated classes, namely, vaccinated susceptible, vaccinated infected, and vaccinated recovered.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, most countries have been providing a 'second opportunity' for measles vaccination (5) such that the national supplementary immunization activities (SIAs) have been considered as a strategic key to increase immunity levels in target populations and to eliminate measles in the entire or large regions (9). Indeed, the Measles and Rubella Initiative focuses on sustaining high vaccination coverage by two-dose routine immunization and supplementing coverage with a second opportunity through SIAs (10). The main purpose of SIAs is to vaccinate all children, who have been missed through the routine vaccination program aged 9 months to 14 years to eliminate any measles susceptibility in the entire population with the periodic follow-up of every 2 to 4 years (2).…”
Section: Introductionmentioning
confidence: 99%